TRADE IN SERVICES - Förster, Andreas (Journal of European Economy, 2017)
Trade in services differs from trade in physical goods. This article highlights some effects of liberalization of trade in services, especially the effects of off-shoring. Many Western European companies settle new branches in Eastern European countries, and this process is known as «off-shoring». This is a new phenomenon discussed in the Western European press, particularly its effects on the labour market. But off-shoring does not only create unemployment in the country where branches were closed. Off-shoring can lead to adjusted wages in the off-shored-sector: after a decline of wages, they can rise again.